Analysis of loading of the boom of a dragline excavator - Brozovsky S.Yu.; Franz T.P.; Lagunova Yu.A.; Shestakov V.S. (Горное оборудование и электромеханика)
The article discusses a method for determining the forces acting on the elements of the boom of a dragline excavator when the bucket is in position, both in the stretch zone and at other points in the working area. The results of the force calculation are used to analyze the stress-strain state of the boom. The research was carried out in the APM WinMachine system in the APM WinStructure3D module. Based on the data from the ESh-20.90 project, a design model has been compiled for a three-gun boom, which includes all the load-bearing elements. Stairs, platforms, support rollers and lighting are taken into account by gravity, inertial and centrifugal forces from the turning movement of the platform. The results of studies of the force and stress-strain state of the boom have proven that, taking into account the forces of gravity, there is no compressive load acting on the upper chord of the boom even when the bucket is as close as possible to the boom, so there is no need to use pre-stressing with cables. Eliminating the cables will simplify the boom design and reduce the cross-section of the upper chord. The results of stress calculations show that there are “excessive” strength reserves; calculations were performed when the wall thick-ness of the pipes of the load-bearing belts was reduced by 1 mm, the strength condition for such sections is ensured, and the mass of the boom will decrease by 7300 kg.